2019
DOI: 10.1186/s13018-019-1473-6
|View full text |Cite
|
Sign up to set email alerts
|

Is deliberate hypotension a safe technique for orthopedic surgery?: a systematic review and meta-analysis of parallel randomized controlled trials

Abstract: BackgroundDeliberate hypotension has been shown to reduce the intraoperative bleeding and the need for allogeneic blood transfusion, and improve the surgical field, but there is still controversy on its clinical safety. This systematic review was designed to assess the safety and benefits of deliberate hypotension for orthopedic surgery.MethodsThe review met the requirements of the PRISMA guidelines. The Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, CINAHL, ISI Web of Science, Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
(61 reference statements)
0
14
0
2
Order By: Relevance
“…The "art" of hypotensive anesthesia is to achieve proper surgical conditions without suppressing perfusion of vital organs [1]. The risk for impairment of tissue perfusion has been the primary concern that limits the use of deliberate hypotension [23]. However, in our patients, we found that PPI did not decrease in the nitroglycerin group throughout the operation, despite the low blood pressure.…”
Section: Discussionmentioning
confidence: 54%
“…The "art" of hypotensive anesthesia is to achieve proper surgical conditions without suppressing perfusion of vital organs [1]. The risk for impairment of tissue perfusion has been the primary concern that limits the use of deliberate hypotension [23]. However, in our patients, we found that PPI did not decrease in the nitroglycerin group throughout the operation, despite the low blood pressure.…”
Section: Discussionmentioning
confidence: 54%
“…In contrast, controlled hypotension during neuraxial anesthesia for joint arthroplasty is usually associated with different pathophysiology. However, its application in orthopedic surgery remains controversial [ 10 ]. Our institution has been practicing neuraxial anesthesia-induced intraoperative controlled hypotension (IOCH) for more than 30 years [ 4 ] with lower blood pressure thresholds in each given case determined at the discretion of the surgeon and anesthesiologist.…”
Section: Introductionmentioning
confidence: 99%
“…Several interventions including deliberate hypotension, the use of antifibrinolytic and preoperative embolization, has been studied in an attempt to minimize the intraoperative bleeding 4,6,7 . Of these methods, super‐selective embolization was considered an optimal technique for blood control in spinal tumor surgery.…”
Section: Introductionmentioning
confidence: 99%